In vitro transfer of methicillin resistance determinants mecA from methicillin resistant Staphylococcus aureus (MRSA) to methicillin susceptible Staphylococcus aureus (MSSA) - Bitrus, Asinamai Athliamai; Zakaria, Zunita; Bejo, Siti Khairani; Othman, Sarah; Ahmad Nadzir, Nur Adilah (BioMed Central, 2017)
Background: Staphylococcus aureus more than any other human pathogen is a better model for the study of the adaptive evolution of bacterial resistance to antibiotics, as it has demonstrated a remarkable ability in its response to new antibiotics. This study was designed to investigate the in vitro transfer of mecA gene from methicillin resistant S. aureus to methicillin susceptible S. aureus. Result: The recipient transconjugants were resistant to erythromycin, cefpodoxime and were mecA positive. PCR amplification of mecA after mix culture plating on Luria Bertani agar containing 100 μg/mL showed that 75% of the donor and 58.3% of the recipient transconjugants were mecA positive. Additionally, 61.5% of both the donor cells and recipient transconjugants were mecA positive, while 46.2% and 41.75% of both donor and recipient transconjugants were mecA positive on LB agar containing 50 μg/mL and 30 μg/mL respectively. Conclusion: In this study, the direction of transfer of phenotypic resistance as well as mecA was observed to have occurred from the donor to the recipient strains. This study affirmed the importance of horizontal transfer events in the dissemination of antibiotics resistance among different strains of MRSA.